Effect of spherical Mo metal particles on microstructure and properties of 316L stainless steel during laser powder bed fusion - Hao Zhang; Lijun Yang; Zhenmeng Zhang; Zhihao Chen; Ziliang Song; Chenyang Wang; Xihui Wu; Xiebin Zhu (Materials Research Express)
Aiming at the performance defects of 316L stainless steel (316LSS), such as low surface hardness, low strength, and poor resistance to chloride ion pitting, Mo/316L particle-reinforced metal matrix composites (PRMMCs) were prepared in this paper using the laser powder-bed fusion (L-PBF) process. It was found that the addition of Mo particles significantly affected the solidification behavior and organization of the matrix and formed a unique spherical metal reinforcement in the matrix, which significantly enhanced the strength of the material while avoiding a serious loss of plasticity: compared with PBF-316L, the ultimate tensile strength (UTS) and elongation of 2Mo/316L with 2 wt% Mo particles added were simultaneously increased by 9.7% and 10.4%, which is a good result of improving strength and plasticity at the same time. With the addition of 6 wt% Mo particles, the UTS of 6Mo/316L reaches 952 MPa while still maintaining a good elongation of 21%. In addition, the hardness, wear resistance and corrosion resistance of the Mo/316L material were significantly improved to varying degrees. This overall improvement in the performance defects of 316LSS is difficult to achieve with other types of reinforcing particles, demonstrating the potential application of using such spherical refractory metal particles for the preparation of PRMMCs in the L-PBF process.